Measuring pro-poor progress towards the non-income millennium development goals - Melanie Grosse; Kenneth Harttgen; Stephan Klasen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
In order to track progress in MDG1 and explicitly link growth, inequality, and poverty reduction, several measures of `pro-poor growth' have been proposed in the literature and used in applied academic and policy work. These measures, particularly the ones derived from the growth incidence curve, allow a much more detailed assessment of the distributional impact of growth and its link to poverty reduction. However, there are no corresponding measures for tracking the distribution of progress in non-income dimensions of poverty, and thus the distribution of progress towards MDGs 2-7. In this paper, we propose to extend the pro-poor growth measurement to non-income dimensions of poverty (particularly health and education). We empirically illustrate the approach for Bolivia and show that it allows a much more detailed assessment of progress towards MDGs 2-7 by focusing on the distribution of progress. Furthermore, this extension also allows an explicit assessment of the linkage between progress in MDG1 and MDGs 2-7 as well as extends traditional incidence analysis by quantifying outcomes in non-income dimensions of poverty along the income distribution.
Keywords: D30; I30; O10; O12; 330; multidimensionality of poverty; Millennium Development Goals; pro-poor growth; growth incidence curve; Bolivia; Armut; Wirtschaftswachstum; Millennium Development Goals; Bolivien